POLITICAL WILL PEMERINTAH KABUPATEN ROKAN HILIR DALAM PEMBANGUNAN JALAN LINTAS KUBU KABUPATEN ROKAN HILIR TAHUN 2016-2020 - Zahwa Juwita; Tito Handoko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Development plays an important role as one of the driving forces for economic growth. Road construction is indispensable as is road infrastructure. In terms of development, in order to achieve equitable development, the Government's Political Will is an important thing needed by every leader of a region in realizing common goals for the benefit of the wider community. The problem of this research is that the development goals are not realized which are not in line with the Political Will of the Rokan Hilir Regency government in the construction of the Kubu crossing, Rokan Hilir Regency. This study generally aims to find out a real picture of how the Government's Political Will in the construction of the Kubu crossing in Rokan Hilir Regency and what are the factors inhibiting the Government in the construction of the Kubu crossing in Rokan Hilir Regency. The research approach used is a qualitative approach and descriptive research type. The location of this research was carried out in Kubu, Rokan Hilir Regency. The data collection technique was done by interview and documentation. The results of this study are that the Political Will or Government commitment in the construction of the Kubu cross road is still lacking and has not been maximized where the government only makes sweet promises, which can be seen that development has not been realized and there are still many obstacles, especially the budget problem of funds and vehicles that have high potential. making the Kubu causeway damaged. Keywords: Government Political Will, Development, Roadways